Union of the Comoros : Report on Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This report on the Observance of Standards and Codes for the Financial Action Task Force (FATF) 40 Recommendations for Anti-Money Laundering (AML) and 9 Special Recommendations on Combating the Financing of Terrorism (CFT) was prepared by the Legal Department of the IMF. It provides a summary of the AML/CFT measures. The assessment is based on the information available at the time of the onsite mission conducted. The views are those of the IMF team and do not reflect the views of the government of the Comoros.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet